A Study on Supply Chain Challenges for the Indian FMCG Sector - Dr. Salim Khan (International Journal of Engineering and Management Research, 2024)
The term "supply chain management" emerged in the 1980s, initially introduced by consultants and later explored by the business community. In simple terms, it establishes an integrated two-way communication system among organizations involved in the supply chain to efficiently manage high-quality inventory. Supply chain management encompasses a network of facilities and distribution options, managing the procurement, transformation, and distribution of materials in both the service and manufacturing sectors. The complexity of supply chains varies across industries and firms, involving multiple end products, shared components, and various transportation modes. SCM facilitates successful supply chain management execution through technology exchange and strategic alliances, collaborating with professional consulting firms and core technology vendors.